Non‐point source pollution modelling using Soil and Water Assessment Tool and its parameter sensitivity analysis in Xin'anjiang catchment, China. Issue 4 (4th February 2013) - Zhai, Xiaoyan; Zhang, Yongyong; Wang, Xuelei; Xia, Jun; Liang, Tao
Abstract Non‐point source pollution is a key issue in integrated river basin management around the world and has resulted in water contamination, aquatic ecology deterioration and eutrophication. Xin'anjiang catchment is the key drinking water source area for Hangzhou City, China. A promising model (Soil and Water Assessment Tool) was applied to assess the non‐point source pollution and its effect on drinking water. Sensitivity analysis of model parameters was carried out using the Sequential Uncertainty Domain Parameter Fitting 2 sensitivity technique. Water discharge, sediment, total nitrogen and total phosphorus load processes from 2000 to 2010 were simulated, and the spatial distributions of non‐point source pollutants were evaluated at the catchment and administrative country levels. The results show that the hydrological parameters of the Soil and Water Assessment Tool were dominantly sensitive for non‐point source pollution simulation, including CN2, RCHRG_DP, ALPHA_BF, SOL_AWC, ESCO and SOL_K and the characteristic parameters of sub‐basins (viz. HRU_SLP and SLSUBBSN). Also, water quality parameters (viz. CH_EROD, NPERCO, RSDCO and PPERCO, PHOSKD, etc.) have a significant effect on nutrients. The model performance was very satisfactory, especially for runoff, sediment and total phosphorus simulation. The non‐point source pollutant load increased from 2001 to 2010 in the whole catchment. Total nitrogen load increased from 3428 tons (0.59 ton km−2) to 7315 tons (1.25 ton km−2), and total phosphorus load increased from 299 tons (0.05 ton km−2) to 867 tons (0.15 ton km−2). The contribution of rice land was the largest, accounting for nearly 95%, followed by tea garden (3.56%), winter wheat (1.37%), forest (0.07%) and grassland (0.02%). Moreover, She County and Xiuning County contributed more than half of the non‐point source pollutants. This study was expected to provide a method and reference for non‐point source pollution quantification and to support water quality management implementation in China. Copyright © 2012 John Wiley & Sons, Ltd.